Varnished fabrics for electrical purposes. Specifications for individual materials. Glass fabric based varnished fabrics with epoxy, polyurethane, silicone, polyester, bituminous or oleoresinous varnish Part 3.2, (15th December 1995) - British Standards Institution,
No abstract available